Turkish foreign policy on Syria, an approach from constructivist point - Çarpar, Özge (My University, 2017)
Since the establishment of Turkey, 1923, there has been efforts to form a homogenous Turkish state identity but there has never been a compromise over Turkey's national identity. Reforms which aimed Westernization and carried by state elites did not get absolute recognition both within the country and from the West. Debates on Turkish identity have increased since the end of Cold War and reached to a climax during the JDP period. Turkey's political development depends on its national identity. Its ability to develop an international role that is proportional to its size and capabilities is also linked to its state identity. This thesis examines implications of a complex and contested Turkish identity that have led to different foreign policy practices in different eras depending on changing nature of Turkish identity. Focusing on diverse actors such as political parties and taking key role of international institutions such as NATO and EU into consideration, this thesis underlines how current foreign policy of Turkey operates in Syrian crisis within constructivist context. This thesis argues that a constructivist account of Turkish foreign policy is more helpful to explain current activism seen in recent Turkish foreign policy conduct during JDP period when we take Turkey's relations with the Middle East, especially changing parameters of relations with Syria in the post Cold War period into consideration. The transition from Turkey's relations with Syria from an enemy to an alliance and then recently a highly problematic relationship is consistent with a a constructivist explanation that takes state identities into consideration to explain the shift in foreign policy choices. It is important to show the connection between Turkish identity and foreign policy preferences by analyzing the preferences of diverse state actors during key periods in Turkish history. This thesis aims to shed light on the relationship between diverse identities of state constructed by political elites, its connection with foreign policy conduct. As indicated through the thesis, the shifts in Turkish foreign policy have resulted from the changes of political elites with different identities in power. An identity based explanation can throw light on the relationship between political actor' own perception of themselves and their comprehensions of others as a key determinant of Turkey's foreign policy choices. This thesis has contributed to the understanding of the formulation of Turkey's foreign policy by showing how diverse state identities and their subjective interactions have shaped Turkish national interests which in turn formulated foreign policy and paved the way for activism in the Middle East especially in Syrian crisis. It also implies that a contested state identity is an obstacle to pursue consistent foreign policy goals by underlining the view that a secure identity is very important to have a stable and powerful role in the international system.

Dış politika davranışlarını devletlerin sosyal olarak kodlanan kimlikleri, çıkarları ve etkileşimleri üzerinden açıklayan İnşacı yaklaşım, kimliğin ve buna bağlı olarak dış politikanın sürekli yeniden inşa süreci ile oluşturulduğunu ifade etmektedir. İnşacı yaklaşımın dış politika tercihlerinin temeline oturttuğu devlet kimliği anlayışından hareketle, bu çalışmada Türkiye’nin değişen politik aktörleri tarafından, yerel ve uluslararası siyasi dinamikler çerçevesinde yeniden inşa edilen devlet kimliği ve buna paralel olarak dış politika davranışlarındaki yeni yönelimleri, Türk dış politikasının aktivizmi ve Suriye krizindeki değişen politik yaklaşımları analiz edilmiştir. Kimlik kurgusundaki dönemsel farklılıkların anlaşılabilmesi ve kimliğin sosyal uzlaşı sonucu politik aktörler tarafından formüle edildiğini ortaya koyması açısından bu çalışma, Türkiye’de politik aktörler tarafından inşa edilen devlet kimliğini, geçmiş dönemlerde inşa edilen devlet kimlikleri ile karşılaştırmıştır. Farklı siyasal aktörler tarafından oluşturulan kimliklerin, farkı dış politika seçimlerine yol açtığını göstermiş, Türkiye’nin Suriye’deki gelişmelere değişen yaklaşımlarını dönemsel olarak ele almıştır. Günümüz Türk dış politikasını analiz etmede kimlik ve ideolojiye dayanan İnşacı yaklaşımın daha açıklayıcı olduğunu ortaya koymuştur. Çalışma kapsamında incelenen Suriye krizi, politik aktörlerin devlet kimliğinde, pratiklerinde ve siyasal söylemlerinde yarattığı dönüşümün dış politikaya nasıl yansıdığının görülmesine olanak tanıyacaktır.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2017
Keywords: Identity; Foreign policy; Syrian crisis; Constructivism; Change